PENELITIAN PENGEMBANGAN MINYAK ATSIRI SEBAGAI AROMATERAPI DAN POTENSINYA SEBAGAI PRODUK SEDIAAN FARMASI - Muchtaridi Dept. TIN (Department of Agroindustrial Technology, Bogor Agricultural University, 2007)
ABSTRACTAromatherapy is a branch of complementary or alternative therapy which is increasing in popularity, yet has scant scientific credibility. Aromatherapy should be defined as treatment using odours and practised as such. However, essential oils are usually used in conjunction with massage and often combined with counselling of some kind. This research is expected to become research methods base in developing of aromatherapy in Indonesia. In this research network, it was found that oil of essential oils is able to be used by aromatherapy divided pursuant to the effect of to center nervous system become three that is softly ( essential oil of kemangi, ki lemo, and lemongrass, cananga), medium ( eucalyptus oil and laja gowah), and hardly (nutmeg seed oil). Analysis of active compound predicted was conducted with integration of SPE-GC/MS which was taken from animal blood after inhalation with essential oils. The active compounds estimated as aromatherapy is 1,8-cineole, linalool, methyl cinnamate, citronellol, citronellal, citral, safrol and mirysticin. On the other hand, this research also formulated pharmaceutical product of aromatherapy in the form of roll-on deodorrant (kemangi oil), cream squeeze ( cananga oil and serai wangi), soap ( oil mixture of kemangi, nutmeg seed, and lemongrass), and functional beverage ( oil of kemangi seeds). The aim of this research network was to prove scientifically the existence of aromatherapy and possibility of development in the field of health.Keywords : aromatherapy, essential oils, SPE-GC/MS